Methodology for determining optimized traffic light cycles based on simulation - Rivera, G. (2020)
In large urbanized cities, a major problem that affects the economy and health of all citizens is vehicular congestion. This is because the traffic light cycles are not adequate. In the present study, we seek to optimize traffic light cycles based on simulation, in order to improve vehicle flow. For this, the PTV Vissim 9.0 software was used as a simulator and the Synchro 10.0 software to determine the initial optimal traffic light cycle. Through several runs and having as variables the length of queues, delay times and the average speed, the optimal traffic light cycle could be found for the study area. The results obtained reflect a 14% reduction in delay times and 10% in queue lengths. On the other hand, the average vehicle speed increased by 10.56%. All this represents an improvement in the service level of the study intersections.